2003
DOI: 10.1016/s0042-6822(03)00384-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural maturation of rubella virus in the Golgi complex

Abstract: Rubella virus is a small enveloped virus that assembles in association with Golgi membranes. Freeze-substitution electron microscopy of rubella virus-infected cells revealed a previously unrecognized virion polymorphism inside the Golgi stacks: homogeneously dense particles without a defined core coexisting with less dense, mature virions that contained assembled cores. The homogeneous particles appear to be a precursor form during the virion morphogenesis process as the forms with mature morphology were the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
47
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 22 publications
5
47
0
1
Order By: Relevance
“…Recently, electron microscopic examination of BUNV-infected cells provided evidence of a "viral factory" in the perinuclear area (45), similar to the factories described for other enveloped viruses (16,38,(43)(44)(45). In addition, the BUNV nonstructural protein NSm also localizes to the Golgi (26,35), which suggested that NSm may be involved in virus assembly and morphogenesis.…”
Section: Discussionsupporting
confidence: 52%
“…Recently, electron microscopic examination of BUNV-infected cells provided evidence of a "viral factory" in the perinuclear area (45), similar to the factories described for other enveloped viruses (16,38,(43)(44)(45). In addition, the BUNV nonstructural protein NSm also localizes to the Golgi (26,35), which suggested that NSm may be involved in virus assembly and morphogenesis.…”
Section: Discussionsupporting
confidence: 52%
“…There are many examples of viral maturation events that occur within the Golgi complex and secretory vesicles (32,44,49,51). Most recently, structural changes in the West Nile virus capsid have been determined by cryo-electron microscopy as the virus particles travel through the low-pH environment of the TGN (72).…”
Section: Vol 81 2007 Dynamic Interactions Of Ul16 With Hsv Capsids mentioning
confidence: 99%
“…Some of these complex viruses use the Golgi apparatus as a key element of the viral factory (41,43,44). The reasons for this preference are not clear since it adds a potential difficulty in terms of efficient transport of large structures, such as viral particles, along the Golgi stack.…”
mentioning
confidence: 99%
“…We have been studying the structure and assembly pathways of several complex enveloped viruses to understand how viral factors interact with cellular elements to generate infectious virions (11,34,40,41,43,44). Bunyaviruses in particular are an adequate structural model to analyze how the viral factory is built and how Golgi factors participate in viral assembly and maturation.…”
mentioning
confidence: 99%